2019
DOI: 10.3390/jmse7100362
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Tidal Stream Turbine Wake Predictions and Analysis of Wake Recovery Mechanism

Abstract: This paper documents the predictive capability of rotating blade-resolved unsteady Reynolds averaged Navier-Stokes (URANS) and Improved Delayed Detached Eddy Simulation (IDDES) computations for tidal stream turbine performance and intermediate wake characteristics. Ansys/Fluent and OpenFOAM simulations are performed using mixed-cell, unstructured grids consisting of up to 11 million cells. The thrust, power and intermediate wake predictions compare reasonably well within 10% of the experimental data. For the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…The reason is that the fine mesh resolution turns on the LES mode of the IDDES. 37 The gap turbulence is mixed with the main flow as it is swept downstream. This phenomenon was also observed previously.…”
Section: Results and Discussion A Inlet Gap Turbulencementioning
confidence: 99%
See 2 more Smart Citations
“…The reason is that the fine mesh resolution turns on the LES mode of the IDDES. 37 The gap turbulence is mixed with the main flow as it is swept downstream. This phenomenon was also observed previously.…”
Section: Results and Discussion A Inlet Gap Turbulencementioning
confidence: 99%
“…29 This setup was validated in the previous study, 30 where turbulence-induced acoustic waves transmitting through a cabin window were simulated. The turbulence is simulated using the IDDES 31 that is combined with the k-x shear stress transport (SST) turbulence model. This setup has been tested in several studies on rotating machinery.…”
Section: Numerical Methodology a Computational Fluid Dynamics (Cfd) Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The objective of this research is to validate the predictive capability of blade-resolved simulations for HKT thrust, power and intermediate wake predictions using flume data [2]. The study builds on the authors' previous blade-resolved HKT validation effort using Ansys/Fluent using RANS, Detached eddy simulation (DES) and LES models [22,29]. Their study demonstrated that, although blade-resolved simulations are sufficiently accurate for HKT thrust and power predictions, they exhibit deficiencies in the prediction of wake recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Globally the interest in marine energy solutions is growing from Europe to Australasia to the Americas. This is reflected in the provenance of the authors of the following papers [1][2][3][4][5].…”
mentioning
confidence: 99%